The Effect of Cinnamon Bark Extract (Cinnamomum burmanii) on Catalase Activity Levels in Hyperglycemic Rats - Perisnawati, Pemi; Yerizal, Eti; Tofrizal, Tofrizal (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2025)
Background: Hyperglycemic is a condition characterized by elevated blood glucose levels, with serum blood glucose levels exceeding 126 mg/dL. Hyperglycemia can induce oxidative stress. Oxidative stress occurs due to an increase in free radicals or a decrease in antioxidant defense activity. Cinnamon bark can enhance antioxidant levels and decrease indicators of oxidative stress. This study examines the impact of cinnamon bark extract on catalase activity levels in hyperglycemic rats. Method: This study used an experimental design with a post-test-only group design. The rats were divided into 5 groups, namely the negative control group (K-), the positive control group (K+), treatment group 1 (dose 100 mg/kgBW), treatment group 2 (dose 200 mg/kgBW) and treatment group 3 (dose 300 mg/kgBW) with 6 rats each. The normality test was carried out using the Shapiro-Wilk test followed by One Way ANOVA. Result: The administration of cinnamon bark extract has been shown to increase catalase activity levels. The most significant increase was observed in dose group 1, with an average of 5.62 Units/mg, which is higher than the control group + (K+), at 3.88 Units/mg. Conclusion: Administration of bark extract has been shown to increase catalase activity in hyperglycemic Rats.